Smartphone-based optical assays in the food safety field - Nelis, J L D; Tsagkaris, A S; Dillon, M J; Hajslova, J; Elliott, C T (Trends in analytical chemistry, 2020)
Smartphone based devices (SBDs) have the potential to revolutionize food safety control by empowering citizens to perform screening tests. To achieve this, it is of paramount importance to understand current research efforts and identify key technology gaps. Therefore, a systematic review of optical SBDs in the food safety sector was performed. An overview of reviewed SBDs is given focusing on performance characteristics as well as image analysis procedures. The state-of-the-art on commercially available SBDs is also provided. This analysis revealed several important technology gaps, the most prominent of which are: (i) the need to reach a consensus regarding optimal image analysis, (ii) the need to assess the effect of measurement variation caused by using different smartphones and (iii) the need to standardize validation procedures to obtain robust data. Addressing these issues will drive the development of SBDs and potentially unlock their massive potential for citizen-based food control.
Keywords: Colorimetric assay; Food safety; Fluorescence assay; Image analysis; Lateral flow immunoassay; Smartphones; Paper-based assay; Portable